Implementasi Teknik Jump Cut dalam Editing Video Reels Instagram pada Akun PLN Icon Plus - Irda Mawar Pratiwi; Alfa Taufan Latif; Fikry Fachrurrizal (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Competition in the information technology industry requires PLN Icon Plus to create innovative communication strategies through Instagram Reels. However, strict internal Standard Operating Procedure (SOP) regulations cause the visual content to be monotonous, overly formal, and distant from social media audiences. This study aims to discuss the implementation of the jump cut editing technique to resolve this issue. The method used is descriptive qualitative with a case study approach. Data collection was conducted through observation, interviews, and document review based on the Stimulus-Organism-Response (S-O-R) theory framework. The results show that using the jump cut technique through extreme clip shortening, fast transitions between talent, instant zoom-ins, and humor-infused text successfully made the videos more interesting and dynamic. These visual changes proved effective in maintaining audience focus and increasing real interactions on Instagram Insights. In conclusion, the jump cut technique is effective in changing stiff corporate content to be more engaging, while still strictly complying with corporate SOP to maintain the company's reputation.